On Raman optical activity sign-switching between the ground and excited states leading to an unusual resonance ROA induced chirality. Issue 3 (25th November 2020) - Machalska, Ewa; Zajac, Grzegorz; Baranska, Malgorzata; Kaczorek, Dorota; Kawęcki, Robert; Lipiński, Piotr F. J.; Rode, Joanna E.; Dobrowolski, Jan Cz.
Abstract : Unusual solute to solvent induced chirality in ROA comes from specific conformer equilibria in the ground and the excited states. Abstract : Raman optical activity (ROA) spectra recorded for a chiral naphthalene diimide derivative (nBu-NDI–BINAM) dissolved in a series of solvents exhibit strong solute to solvent induced chirality with: (1) dominating bands of solvents, (2) n Bu-NDI–BINAM resonance ROA (RROA) bands which are barely visible, (3) monosignate RROA Solvent spectra with an unexpected sign concordant with that of the ECD band of the resonant electronic state, (4) bisignate RROA bands for a few solvents, and (5) superposition of non-resonant and resonant ROA bands of the chiral solvents. The unusual ROA enhancement was explained in terms of resonance energy transfer with resonant Raman emission. The surprising RROA sign-switching was found to be due to specific conformational equilibria where one solute conformer dominates in the ground and the other in the first excited singlet state, and, the signs of the related ECD bands of these two conformers are opposite.